THE APPLICATION OF THE SEMIOTICS OF QUR’AN TOWARD THE STORY OF THE CHOSEN SERVANTS IN SURAH MARYAM - Soga, Zainuddin; Mardan, Mardan; Tola, Achmad; Kasim, Amrah; Abunawas, Kamaluddin (Jurnal Diskursus Islam, 2021)
This study elaborates the application of semiotic theory in Surah Maryam (Maryam). This study is library research. The library research was conducted through various literature studies related to the problem investigated. The approach used is a semiotic approach. The data sources are divided into two; primary and secondary data. The primary data source is the Qur'an (surah Maryam) and the secondary data sources are books of interpretation, semiotics and linguistics. The data collection is done by quoting, adapting, and analyzing the representative literature and relevant to the problems discussed, then reviewing and concluding. The study results showed three forms of semiotic application in Surah Maryam: first, semiotics of significance from Ferdinand de Saussure's (synchronic-diachronic theory). Second, semiotics of communication from Charles S. Peirce's includes iconic, indexical, and symbolic theories. Third, connotative semiotics from Roland Barthes' which consists of denotative meaning and connotative meaning. This study implies that the semiotic reading of the Qur’an prioritizes the interpretation of the text in a synchronic and diachronic, denotative and connotative way. Hopefully, by this reading, religious and Islamic moderation could be achieved.